Revealed wisdom and inaugurated eschatology in ancient Judaism and early Christianity - Macaskill, Grant. (Supplements to the Journal for the Study of Judaism, 2007)
This book examines four texts: 1 Enoch, 4QInstruction, Matthew and 2 Enoch. A common idea in these texts, which blend sapiential and apocalyptic elements, is that the revealing of wisdom to an elect group inaugurates the eschatological period. The emphasis on "revealed wisdom" is essentially apocalyptic, but facilitates the uptake of motifs, forms and language from the sapiential tradition and is important in explaining the fusion of the two traditions. In addition, revealed wisdom often has creational associations and this has significance for the notion of ethics in these texts. The book will interest anyone concerned with the development of Jewish and Christian eschatology and ethics. It also challenges the simplistic redactional assumptions of certain New Testament scholars.